2020
DOI: 10.1103/physrevfluids.5.023502
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent rotating convection confined in a slender cylinder: The sidewall circulation

Abstract: Recent studies of rotating Rayleigh-Bénard convection at high rotation rates and strong thermal forcing have shown a significant discrepancy in total heat transport between experiments on a confined cylindrical domain on the one hand and simulations on a laterally unconfined periodic domain on the other. This paper addresses this discrepancy using direct numerical simulations on a cylindrical domain. An analysis of the flow field reveals a region of enhanced convection near the wall, the sidewall circulation. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
86
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 41 publications
(100 citation statements)
references
References 36 publications
8
86
0
Order By: Relevance
“…Note that de Wit et al (2020) also measured the drift frequency as a function of Ra and found the following fit: ω d ≈ −6 × 10 −10 Ra 1.16±0.06 E (using our rotation units). Using the same approach as in section 3, we measured the drift frequency in our simulations below the onset of the bulk mode and in figure 4(c) we compare the results with the fit of de Wit et al (2020). The results clearly bridge the gap between the onset theoretical value derived by Herrmann & Busse (1993) and the highly turbulent scaling found by de Wit et al (2020).…”
Section: Link With Recent Experiments and Simulations At High Ramentioning
confidence: 51%
See 4 more Smart Citations
“…Note that de Wit et al (2020) also measured the drift frequency as a function of Ra and found the following fit: ω d ≈ −6 × 10 −10 Ra 1.16±0.06 E (using our rotation units). Using the same approach as in section 3, we measured the drift frequency in our simulations below the onset of the bulk mode and in figure 4(c) we compare the results with the fit of de Wit et al (2020). The results clearly bridge the gap between the onset theoretical value derived by Herrmann & Busse (1993) and the highly turbulent scaling found by de Wit et al (2020).…”
Section: Link With Recent Experiments and Simulations At High Ramentioning
confidence: 51%
“…Despite this, we show here that these modes bear all the hallmarks of topologically protected states. We first show -in a cylindrical geometry -that these modes are robust with respect to secondary instabilities and to a turbulent bulk state as in the experiments (de Wit et al 2020;Zhang et al 2020) by gradually increasing the Rayleigh number until the bulk becomes turbulent. Second, we show that these states persist in the presence of different types of barriers, and show that the wall modes happily follow whatever boundary geometry is provided.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations